STUDENTS' UNDERLINING HABIT: IS THERE A CORRELATION WITH READING COMPREHENSION? - Ghea Azzahra (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2021)
This study investigated the frequency of students' habit of underlining text and the correlation between the habit and their reading comprehension. Quantitative research was carried out with specific purposes on 73 first-semester students at department of English Language Education (PBI) of Ar-Raniry University (UIN). Based on the Likert scale, the data analysis of the questionnaire showed 72.9% of students had a good underlining habit, followed by the percentage of comprehension test was 65.8%. Moreover, the Pearson formula resulted from the correlation coefficient was 0.699 that indicated both variables had a high correlation.